2019
DOI: 10.1155/2019/9181758
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access and Utilization of Maternal Healthcare Services through Focused Antenatal Care in Rural Ghana: A Qualitative Study

Abstract: Improved access to and utilization of various maternal healthcare services have been seen as the panacea to poor maternal and child health outcomes characterizing many developing countries. Focused Antenatal Care (FANC) replaced the regular antenatal care model about a decade and a half ago. This study sought to document empirical outcomes of how the FANC approach translates access and utilization of maternal health services into positive maternal health outcomes. We utilized a descriptive qualitative design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 29 publications
5
43
0
Order By: Relevance
“…Hjortsberg and Mwikisa (2002) found in the case of Zambia (with similar health and demographic characteristics as Ghana) that the poor are less likely to seek healthcare when ill than the non‐poor and that distance to health facilities has an impact on utilisation, where nearly 50 per cent of people living less than 5 km from a health facility will seek healthcare when ill, compared with 17 per cent of people living more than 40 km from a health facility. Similar findings emerged in Ghana where transportation difficulties have been cited as a barrier to healthcare access in rural areas (Macha et al, 2012; Masters et al, 2013; Johnson et al, 2015; Nesbitt et al, 2016; Haruna, Dandeebo, & Galaa, 2019). Thus, whereas the relationship between transportation difficulties and limited access to healthcare has received research attention, the issues of costs relating to food and lodging during admissions have not been investigated in the specific context of the NHIS.…”
Section: Equity and Affordability Of Healthcaresupporting
confidence: 63%
See 1 more Smart Citation
“…Hjortsberg and Mwikisa (2002) found in the case of Zambia (with similar health and demographic characteristics as Ghana) that the poor are less likely to seek healthcare when ill than the non‐poor and that distance to health facilities has an impact on utilisation, where nearly 50 per cent of people living less than 5 km from a health facility will seek healthcare when ill, compared with 17 per cent of people living more than 40 km from a health facility. Similar findings emerged in Ghana where transportation difficulties have been cited as a barrier to healthcare access in rural areas (Macha et al, 2012; Masters et al, 2013; Johnson et al, 2015; Nesbitt et al, 2016; Haruna, Dandeebo, & Galaa, 2019). Thus, whereas the relationship between transportation difficulties and limited access to healthcare has received research attention, the issues of costs relating to food and lodging during admissions have not been investigated in the specific context of the NHIS.…”
Section: Equity and Affordability Of Healthcaresupporting
confidence: 63%
“…Cost of access remains a significant barrier to poor populations especially those in rural areas when they become ill and need to seek healthcare. Studies in developing countries (Hjortsberg & Mwikisa, 2002; Målqvist et al, 2010; Gabrysch, Cousens, Cox, & Campbell, 2011; Lohela, Campbell, & Gabrysch, 2012) including Ghana (Macha et al, 2012; Masters et al, 2013; Johnson et al, 2015; Nesbitt et al, 2016; Haruna et al, 2019) have shown that proximity to health facilities strongly influences healthcare use. In these contexts, however, distances to health facilities are often long, health‐related infrastructure is poor and a significant proportion of the population live in poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Two‐thirds of maternal mortality in low and middle income countries occur due to direct obstetric complications . Antenatal care, skilled birth attendance at delivery and post‐natal care are critical ingredients in preventing maternal deaths . Despite this knowledge, in 2016 at national level, only 62% of women attended at least one antenatal care session, only 26 % of deliveries were assisted by a skilled birth attendant, and only 49% of women had their last birth protected against neonatal tetanus in Ethiopia .…”
Section: Introductionmentioning
confidence: 99%
“…This study shows that majority of the pregnant Female doctors more than two in OPD at RHC 100% females used government hospitals for antenatal care. A study conducted by Umar Haruna shows that utilization of antenatal care is increasing [9]. The current study shows that accessibility of maternal health services have many challenges in terms of quality of maternal health care, availability of maternal health care etc.…”
Section: Data Collection Proceduresmentioning
confidence: 69%